Analisa Kebijakan Hukum Terhadap Kasus Koin Kripto Sebagai Bukti Elektronik Tindak Kejahatan Pencucian Uang - Murti, Terra Whisnu; K, Kefianto; Ferdiansyah, Reza; Priyambodo, Muhammad Bagus; Akbar, Masyhur; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
The presence of the bitcoin concept, especially blockchain technology, first attracted the world's attention and provided good opportunities. However, in fact it is increasingly opening up loopholes for criminals, one of which is money laundering. Currently, crimes involving money laundering on blockchain platforms have accumulated significant amounts and caused considerable losses. In terms of the regulation of the criminal act of money laundering, there are still obstacles that give rise to pros and cons in the investigation process carried out by law enforcers, thus giving rise to problems in the investigation process. Therefore, this research examines whether investigators can prove and reveal criminal acts of money laundering which currently can only reach people who participate in committing criminal acts and what is the model for investigating criminal acts of money laundering which can confiscate, confiscate and destroy the assets of perpetrators of the crime. money laundering crime carried out using advanced technology and cryptocurrency. This research uses a normative legal research method which examines law conceptualized as applicable norms or rules.